2016
DOI: 10.1149/07509.0053ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) High Output Power Deep Ultraviolet Light-Emitting Diodes with Hemispherical Lenses Fabricated Using Room Temperature Bonding

Abstract: We reviewed the structural and optical properties of high output power 255 and 280 nm light-emitting diodes (LEDs) bonded with hemispherical lenses made of inorganic materials. [This is described as a full paper (and not a review). Is this your intended meaning?][This is my intended] The optimal LED structure with a lens to improve the output power for deep ultraviolet LEDs was designed using Monte Carlo simulation. The LED chips were bonded to sapphire lenses at room temperature using either atomic diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…Ichikawa et al [27] reported the application of hemispherical sapphire lenses bonded to the substrates of DUV LED chips to enhance the light extraction efficiency. The 255 nm DUV LEDs with a sapphire lens fabricated using the surface activated bonding method showed a light extraction efficiency enhancement of 2.8 times when compared to a reference LED lacking the lens, and an EQE of 4.56% was achieved.…”
Section: Device Design For Improved Performance Of Group Iii-nitride mentioning
confidence: 99%
“…Ichikawa et al [27] reported the application of hemispherical sapphire lenses bonded to the substrates of DUV LED chips to enhance the light extraction efficiency. The 255 nm DUV LEDs with a sapphire lens fabricated using the surface activated bonding method showed a light extraction efficiency enhancement of 2.8 times when compared to a reference LED lacking the lens, and an EQE of 4.56% was achieved.…”
Section: Device Design For Improved Performance Of Group Iii-nitride mentioning
confidence: 99%
“…[1] Ichikawa et al [23] have reported the application of hemispherical sapphire lenses bonded to the substrates of DUV LED chips to enhance the light extraction efficiency. The 255 nm DUV LEDs with a sapphire lens fabricated using the surface activated bonding method have shown a light extraction efficiency enhancement of 2.8 times when compared to a reference LED lacking the lens, and an EQE of 4.56% was achieved.…”
Section: Device Design For Improved Performance Of Group Iii-nitrde Dmentioning
confidence: 99%
“…Deep-UV light with an emission wavelength below 290 nm can rapidly inactivate the deoxyribonucleic acid of virus and bacteria [4,5]; however, the light-emission efficiency (LEE) of deep-UV LEDs is considerably lower than that of low-pressure mercury lamps. The wall-plug efficiency of mass-produced deep-UV LEDs is a maximum of 10% because of the UV light absorption of the p-type gallium nitride (GaN) contact layer [6][7][8]. A p-type GaN contact layer is used Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%